2015
DOI: 10.1016/j.eurpsy.2014.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Apathy in Nursing Home Residents with Dementia: Results From A Cluster-Randomized Controlled Trial

Abstract: Our intervention was effective for the therapy of apathy in dementia, when applied, but not one year after cessation of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 35 publications
2
30
0
2
Order By: Relevance
“…The level of apathy was lower in the exercise group after the intervention vs control group. Treusch et al conducted a 10‐month RCT in 117 patients and found that increase in apathy AES scores was significantly reduced in a “biography‐orientated mobilization” group vs control group. In a study by Valenti Soler et al, patients with dementia who came in contact with social robots exhibited an improvement in NPI apathy scores.…”
Section: Resultsmentioning
confidence: 99%
“…The level of apathy was lower in the exercise group after the intervention vs control group. Treusch et al conducted a 10‐month RCT in 117 patients and found that increase in apathy AES scores was significantly reduced in a “biography‐orientated mobilization” group vs control group. In a study by Valenti Soler et al, patients with dementia who came in contact with social robots exhibited an improvement in NPI apathy scores.…”
Section: Resultsmentioning
confidence: 99%
“…Despite increased interest in the treatment of apathy, results of intervention studies are inconsistent and no treatment has yet been established. Recent research has targeted medical treatment, deep brain stimulation of the subthalamic nucleus, and psychosocial treatment (cognitive rehabilitation, psychotherapy, activity, and occupational therapy) …”
Section: Discussionmentioning
confidence: 99%
“…Whilst physical therapy (Treusch et al, 2015;Potter et al, 2011) had no demonstrable impact on mood, Padilla et al (2011) concluded there was evidence for short-term modest benefit from the varied environmental interventions they reviewed, and Subramaniem and Woods (2012) and Kolanowksi (2011) also concluded there were some positive benefits from reminiscence and need-based activities, in the latter case for general affect rather than depressed mood. Yoga also had a positive effect (Fan & Chen, 2011).…”
Section: Table 5 About Herementioning
confidence: 99%